Strong subordination and superordination with sandwich-type theorems using integral operators - ARJOMANDINIA, Parviz; AGHALARY, Rasoul (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
The notions of strong differential subordination and superordination have been studied recently by many authors. In the present paper, using these concepts, we obtain some preserving properties of certain nonlinear integral operator defined on the space of normalized analytic functions in D×D. The sandwich- type theorems and consequences of the main results are also considered. Mathematics Subject Classification (2010): 30C45, 30C80.